A study on factors affecting on consumers' fast foods buying behaviour: reference to pizza hut in the anuradapura city area, sri lanka - Udurawana, Y.M.W.G.P.K. (university of Jaffna, 2014)
This explorative study conducted to identify factors affecting on consumers fast foods buying behavior with special reference to Pizza Hut outlet in Anuradhapura city area. The study population represented by each and every customer located in Anuradhapura city area and representative sample was selected including school children to foreigners and entrepreneurs those who have consumed pizza. 114 members out of 120 responded to the researcher, where they ware contributed to examine nine variables was Location, Atmosphere, Sales Persons Behavior, Awareness, Price, Quality, Image, Promotion, Fast Service with demographic variables and the required data was collected through structured questionnaires. Data was analyzed through descriptive techniques where percentages, mean, standard deviation, t test and cross tabulation ware facilitated. At the end researcher identified that all factors ware significant towards consumer buying behavior but related to the selected region customers was not satisfactory awareness about various brands of pizza, culture of pizza; location was confused on parking and low freedom even with atmosphere. And they enjoyed their image though consuming pizza appreciating sales person behavior but pricing, nutrition and promotion ware somewhat deviated on consumer expectation related to the analysis. Finally researcher suggested to change location of pizza outlets and commented to increase awareness of consumers related pizza culture.
Keywords: Pizza hut; Fast foods; Consumer behavior